Spectral theory of natural unidirectionality of SPUDT for BG waves - DANICKI, E. (Archives of Acoustics, 1991)
A single-phase unidirectional interdigital transducer SPUDT is modelled by a system of periodic metal strips on a piezoelectric halfspace carrying Bleustein-Gulyaev BG wave. The dispersion relation for BG surface wave, as well as some relations between forward and backward waves in the system are discussed. Natural unidirectionality is explained in this way.